Methodology Needs Analytics: A Rejoinder to Martyn Hammersley - Speer, Susan A.; Hutchby, Ian (Sociology (Oxford), 2003)
The authors respond to comments from Hammersley (2003) regarding their paper From Ethics to Analytics: Aspects of Participants' Orientations to the Presence and Relevance of Recording Devices (2003). They challenge the distinction Hammersley draws between methodology and analytics. Reflexivity is an approach which highlights the necessary connection between methodology and analytics. Indeed, by turning a methodological concern with reactivity into an analytic question, one may gain a better understanding of the ways in which research and research impact upon data. Analytics in this sense do not replace methodology or signal the abandonment of methodological concerns, but feed back into and lend empirical weight to important methodological debates. A methodological commitment to reflexivity means very little unless one possesses the analytic resources to put such reflexivity into practice in an convincing way, and thus produce findings about reactivity that are actually borne out by one's data.